The Youth Sports and Tourism Office’s Function in Baraka District, Enrekang Regency’s Tourism Development - M. Aswad Hasta; Andi Niartiningsih; Andi Muhammad Rusli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Enrekang Regency's Baraka District is a sub-district classified as a natural tourism destination. The issue confronting the development of the Baraka District as a tourist destination is the inadequate management of tourism potential. As a result, the purpose of this research is to examine the role of the Enrekang Regency Youth and Sports Office in the development of tourism in the Baraka District. This research was conducted for three months at the Department of Youth, Sports, and Tourism in Enrekang Regency and Baraka District. Researchers' initial issue formulation analysis tool included three stages: data reduction, data presentation, data verification, and generating conclusions. SWOT analysis is the second analytical tool utilized by academics. According to the findings, the Youth, Sports, and Tourist Office played five roles in tourism development in Baraka District, Enrekang Regency: motivators, communicators, facilitators, mediators, and dynamists. The Youth, Sports, and Tourism Office's strategy in Tourism Development in Baraka District, Enrekang Regency through a SWOT analysis with a weighting score of 0-100 very poor, 100-200 less, 200-300 enough, 300-400 good, 400-500 very good indicating that in the Strength aspect, Baraka District has tourism potential that can be developed with a weighting score of 330. With a weighted score of 260, the government's tourism village development initiatives are a weakness with a weighting value of less than 300. Opportunities aspects to develop tourism potential are quite large by a weighting score of 330. And Threats with a weighted score of 270.